High-transparency insulating anti-corrosion heat-dissipation self-cleaning film as well as preparation method and application thereof
By using modified nanobarium sulfate and nano-oxide metal compositions, combined with specific emulsions and functional additives, the waterproof, anti-static and aging resistance of the high-transparent insulation anti-corrosion and heat dissipation self-cleaning film is improved, and the performance of existing membrane materials is solved. The problem of insufficient achieves higher comprehensive performance and equipment protection effect.
Patent Information
- Application Number
- CN202411520760.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing high-transparent insulation anti-corrosion and heat dissipation self-cleaning film has shortcomings in waterproof, anti-static, aging resistance, mechanical and mechanical properties, and cannot meet the needs of electronic components, electronic products, photovoltaic inverters, motors, cabinets, wires and cables, boilers. , high-temperature pipelines and other fields of diversified performance requirements.
Using modified nanobarium sulfate, nano cerium oxide, nano alumina and nano zirconia compositions, combined with a composition of modified acrylic emulsion and ethylene vinyl acetate fat and polyvinyl methyl ether, the surface group activity is modified and combined The structure is formed to enhance the molecular connection force and mechanical mechanical properties of the film layer, and epoxy block polyether and arylphenol polyoxyethylene ether are added to improve waterproof, oilproof, saltproof and aging resistance.
While maintaining excellent insulation, heat dissipation, corrosion and self-cleaning performance, it improves the waterproof, aging resistance and anti-static properties of the film layer, extends the service life of the equipment, reduces the cost of use, and significantly improves the integration of the film layer. performance.
Smart Images

Figure BDA0005107994170000151 
Figure BDA0005107994170000161
Abstract
Description
Technical Field
[0001] The present application relates to the field of membrane materials, and in particular to a highly transparent insulating, anti-corrosion, heat-dissipating, self-cleaning membrane and a preparation method and application thereof. Background Art
[0002] At present, the diverse performance requirements for insulation, anti-corrosion, heat dissipation and self-cleaning in the fields of electronic components, electronic products, photovoltaic inverters, motors, cabinets, wires and cables, boilers, high-temperature pipelines, etc. cannot be achieved on a single product. However, with the development of science and technology, higher requirements are put forward for the performance of related products in the fields of electronic components, electronic products, photovoltaic inverters, motors, cabinets, wires and cables, boilers, high-temperature pipelines, etc., and the emerging technical direction of high-transparency insulation, anti-corrosion, heat dissipation and self-cleaning film has gradually entered people's field of vision.
[0003] Highly transparent insulation, anti-corrosion, heat dissipation and self-cleaning film is a high-performance functional film layer. It is a protective film for electronic products, photovoltaic inverters, motors, cabinets, wires and cables, boilers, high-temperature pipes and other related products. It is usually made of high-quality resin materials. Its main function is to provide an additional protective layer without affecting the appearance to improve the heat dissipation function of the product; insulation function: people and objects are not affected and harmed by conductivity, and factors that affect safety and the poor operation of surrounding equipment are overcome; anti-corrosion function makes the appearance intact and keeps the equipment in good working condition; self-cleaning properties mean that this film has a certain ability to reduce the adhesion of dirt, dust and other pollutants, or make these pollutants easier to clean, which is usually due to special treatment or coating on the surface of the film. At the same time, the existing high-transparency insulation, anti-corrosion, heat dissipation and self-cleaning films still have good performance in terms of waterproof, antistatic, aging resistance and mechanical mechanical properties.
[0004] Therefore, in order to solve the above problems, the present application provides a highly transparent insulating, anti-corrosion, heat-dissipating, self-cleaning film and a preparation method thereof. The highly transparent insulating, anti-corrosion, heat-dissipating, self-cleaning film prepared in the present application can maintain excellent insulation, heat dissipation, anti-corrosion, self-cleaning properties and mechanical properties while maintaining good waterproof, aging resistance and anti-static properties. It meets the performance requirements of related products in the fields of existing electronic components, electronic products, photovoltaic inverters, motors, cabinets, wires and cables, boilers, high-temperature pipelines, etc., achieves better comprehensive performance and extends service life, has good energy-saving effects, reduces the cost of use, and has very excellent application prospects. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present application provides a highly transparent insulating, anti-corrosion, heat-dissipating and self-cleaning film. The raw materials, calculated by mass, are: 20 to 40 parts of base emulsion, 30 to 60 parts of nanoparticles, 10 to 20 parts of functional additives, 20 to 30 parts of diluents, 15 to 25 parts of silicone oil, 1 to 3 parts of leveling agents, 2 to 5 parts of wetting agents, and 1 to 3 parts of dispersants.
[0006] As a preferred solution, the mass ratio of the base emulsion, the nanoparticles and the functional additive is (30-38): (35-45): (12-18).
[0007] As a preferred solution, the mass ratio of the base emulsion, the nanoparticles and the functional additive is (33-36): (38-42): (14-16).
[0008] As a preferred solution, the mass ratio of the base emulsion, the diluent and the silicone oil is (30-38): (22-26): (18-24).
[0009] As a preferred solution, the mass ratio of the base emulsion, the diluent and the silicone oil is (33-36): (24-25): (20-22).
[0010] As a preferred solution, the base emulsion is a composition of modified acrylic emulsion, ethylene vinyl acetate and polyvinyl methyl ether.
[0011] As a preferred solution, the mass ratio of the modified acrylic emulsion and the modified acrylic emulsion to ethylene vinyl acetate and polyvinyl methyl ether is (2-5): (0.8-1.2); (0.5-1.0).
[0012] As a preferred solution, the modified acrylic emulsion is an organosiloxane-modified acrylic emulsion.
[0013] As a preferred solution, the viscosity of the modified acrylic emulsion is 150-300 mPa·s at 25°C.
[0014] As a preferred solution, the solid content of the modified acrylic emulsion is 50-55 wt %.
[0015] As a preferred solution, the nanoparticles are a composition of modified nano-barium sulfate, nano-cerium oxide, nano-aluminum oxide and nano-zirconium oxide.
[0016] As a preferred solution, the mass ratio of the modified nano-barium sulfate, nano-aluminum oxide and nano-zirconium oxide is (2-2.5): (1.5--2) (1-1.4): (1-1.4).
[0017] As a preferred solution, the average particle size of the modified nano-barium sulfate is 20 to 30 nm.
[0018] As a preferred solution, the average particle size of the nano-cerium oxide is 10 to 20 nm.
[0019] As a preferred solution, the average particle size of the nano-alumina is 10 to 20 nm.
[0020] As a preferred solution, the average particle size of the nano zirconium oxide is 10 to 20 nm.
[0021] The preparation method of the modified nano barium sulfate comprises the following steps: adding barium sulfate into a mixed solvent: dimethylformamide and dihexylene triamine pentyl acetic acid (DTPA), dispersing into a solution, adding a modifier to modify the barium sulfate, and finally filtering, drying, sieving, and airflow classification to obtain the modified nano barium sulfate.
[0022] As a preferred solution, the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0023] As a preferred solution, in the mixed solvent of ethanol and isopropanol, the mass ratio of ethanol to isopropanol is (1-1.5):(4-4.5).
[0024] As a preferred solution, the average particle size of the nano-cerium oxide is 10 to 20 nm.
[0025] As a preferred solution, the average particle size of the nano-alumina is 10 to 20 nm.
[0026] As a preferred solution, the average particle size of the nano zirconium oxide is 10 to 20 nm.
[0027] As a preferred solution, the average particle size of the modified nano-barium sulfate is 20 to 30 nm.
[0028] The modified nano barium sulfate and nano cerium oxide, nano aluminum oxide and nano zirconium oxide combination scheme added in the present application can effectively improve the high efficiency heat dissipation performance of the heat dissipation self-cleaning film, and the composition of modified acrylic emulsion and ethylene vinyl acetate and polyvinyl methyl ether can improve high transparency, corrosion resistance, insulation, waterproof and moisture-proof, self-cleaning performance, etc., thereby maintaining good high transparency insulation corrosion resistance heat dissipation self-cleaning performance. The modified nano barium sulfate particles can form composite particles with framework particles as the internal main body and nano barium sulfate as the outer layer through the bonding action of coordination bonds, so that the particles can enhance the connection force with the molecules of the film system through the active modification of the surface groups, thereby achieving uniform dispersion in the film layer and particle stability after curing, avoiding segregation and agglomeration. On the other hand, the formed composite structure can guide the contact between the nano cerium oxide particles, nano aluminum oxide particles, and zirconium oxide particles in the film layer and the framework particles through the guiding effect of the surface nano barium sulfate particles on other nano particles, thereby achieving the modified acrylic emulsion for various stability adsorption, and the film layer maintains good heat dissipation function under normal conditions.
[0029] In addition, the modified nano-barium sulfate particle structure can play a good supporting role when the membrane layer is subjected to external force based on the skeleton structure of the frame particles, and because of the connection between the surface ethylene vinyl acetate, polyvinyl methyl ether composition and the organic molecules of the membrane layer, it plays a certain tensile connection role, maintaining good mechanical properties of the membrane layer; on the surface of the membrane layer, the extremely low surface energy of the composite particle structure can promote smoother, and the surface of the membrane layer of the composition of ethylene vinyl acetate and polyvinyl methyl ether is formed, so that the insulation function and self-cleaning function can be realized; and the smoother membrane layer surface greatly reduces the adhesion of dust and other pollutants, or makes these pollutants easier to clean up, which is usually due to the special treatment of the membrane surface or the retention time of dust and other pollutants on the coating surface on the membrane layer surface, and thus dust and other pollutants cannot be gathered in a short time, so that the surface of the equipment remains clean; in most application environments, dust and other pollutants are removed by gravity due to the smooth surface effect and high hydrophobicity, thereby obtaining excellent membrane self-cleaning, waterproof, oil-proof, salt-proof, corrosion-resistant, aging-resistant and other properties.
[0030] As a preferred solution, the functional auxiliary agent is a composition of polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether.
[0031] As a preferred solution, the mass ratio of the polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether is (4-5): (3-3.5): (1-2).
[0032] As a preferred solution, the mass ratio of the polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether is (4.2-4.5): (3.2-3.3): (1.2-1.5).
[0033] As a preferred solution, the weight average molecular weight of the polyethylene glycol methyl ether is 400 to 800 Da.
[0034] As a preferred solution, the weight average molecular weight of the epoxy block polyether is 6000-8000 Da.
[0035] As a preferred solution, the ethylene oxide block content of the epoxy block polyether is 60 to 70 wt%.
[0036] As a preferred solution, the aromatic phenol polyoxyethylene ether is a combination of phenethylphenol polyoxyethylene ether and trimethylstyrenephenol polyoxyethylene ether.
[0037] As a preferred solution, the mass ratio of the phenethylphenol polyoxyethylene ether to the trimethylstyrenephenol polyoxyethylene ether is (3-4): (0.6-0.8).
[0038] As a preferred solution, the HLB value of the phenethylphenol polyoxyethylene ether is 10-12.
[0039] As a preferred solution, the HLB value of the trimethylstyrene phenol polyoxyethylene ether is 15-18.
[0040] The above-mentioned composite functional additives added in the present application can effectively assist in improving the mechanical properties of the film layer, and can effectively ensure the waterproof and aging corrosion resistance of the self-cleaning film. The epoxy block polyether and polyethylene glycol methyl ether added in the present application can enhance the molecular network construction assistance effect of the overall functional additives in the film material by embedding the effect of different molecular chain lengths, thereby enhancing the tightness of the internal three-dimensional network of the film layer, and molecular chains of different lengths are easy to form entanglements with each other, which helps to improve the intermolecular force, and then assist in improving the mechanical properties of the film layer, and the addition of arylphenol polyoxyethylene ether can effectively reduce the agglomeration of each nanoparticle added in the present application, so as to better use epoxy block polyether and polyethylene glycol methyl ether as dispersion carriers in the formation of the film layer, thereby enhancing the uniformity of each particle in the film layer, and can avoid the formation of large particle micropores caused by particle agglomeration, thereby affecting the connection between molecules and particles, and finally reducing friction mechanical properties. On the other hand, the compounded functional additives can also assist the formation of a smooth film surface of the composition of ethylene vinyl acetate and polyvinyl methyl ether on the surface, thereby achieving the overall film layer's self-cleaning, waterproof, oil-proof, salt-proof, corrosion-resistant, aging-resistant and other properties.
[0041] As a preferred solution, the diluent is at least one of ethanol, methanol, isopropanol or ethyl acetate.
[0042] As a preferred solution, the diluent is ethanol or isopropanol.
[0043] As a preferred solution, the leveling agent is at least one of organic silicon leveling agents.
[0044] As a preferred solution, the leveling agent is an organic silicon leveling agent BYK-306.
[0045] As a preferred solution, the wetting agent is at least one of non-ionic wetting agents.
[0046] As a preferred solution, the dispersant is at least one of polyurethane, acrylic and betaine.
[0047] As a preferred solution, the dispersant is polyurethane or acrylic.
[0048] As a preferred solution, the dispersant is acrylic BYK-163.
[0049] The second aspect of the present application provides a method for preparing the above-mentioned highly transparent insulating, anti-corrosion, heat-dissipating and self-cleaning film, and the specific steps include the following steps: S1: Add diluent, functional additive, silicone oil and base emulsion into a high-speed mixer, and stir at 1200-1800 rpm for 10-20 minutes until uniform; S2: After adding the nanoparticles, continue to maintain a speed of 1200-1800 rpm and stir for 15-25 minutes; S3: Finally, add leveling agent, wetting agent and dispersant at a speed of 800-1000 rpm, stir for 8-10 minutes, and after completion, coat the mixture on the desired substrate surface, heat to 60-80°C and cure for 4-6 hours to obtain the product.
[0050] The second aspect of the present application provides an application of the above-mentioned highly transparent insulating anti-corrosion heat dissipation self-cleaning film in products related to the fields of electronic components, electronic products, photovoltaic inverters, motors, cabinets, wires and cables, boilers, high-temperature pipelines, etc.
[0051] The beneficial effects of this application are:
[0052] 1. The highly transparent insulating, anti-corrosion, heat-dissipating and self-cleaning film provided in the present application can maintain excellent insulation, heat dissipation, anti-corrosion, self-cleaning and mechanical properties while maintaining good waterproof, oil-proof, aging-resistant and anti-static properties; it not only meets the diverse performance requirements of related products in the fields of existing electronic components, electronic products, photovoltaic inverters, motors, cabinets, wires and cables, boilers, high-temperature pipelines, etc., but also plays an excellent protective, energy-saving and comfortable role in people's daily life, achieving better comprehensive performance and extending the service life of equipment, and has very excellent application prospects.
[0053] 2. The highly transparent insulating, anti-corrosion, heat-dissipating, self-cleaning film provided in the present application, the added modified nano-barium sulfate can enhance its connection force with the molecules of the film system through the active modification of the surface groups, thereby achieving uniform dispersion in the film layer and stability of the particles after solidification, avoiding segregation and agglomeration. On the other hand, the formed composite structure can guide the heat source to quickly extract heat through the heat dissipation effect of the surface barium sulfate particles, thereby achieving an advanced thermal conductivity.
[0054] 3. A highly transparent insulating, anti-corrosion, heat-dissipating, self-cleaning film provided in the present application has a modified nano-barium sulfate particle structure added thereto, which can play a good supporting role when the film layer is subjected to external force based on the skeleton structure of the framework particles, and because of the connection between the surface-modified nano-barium sulfate and the organic molecules of the film layer, it plays a certain tensile connection role, thereby maintaining good mechanical properties of the film layer; and on the surface of the film layer, the extremely low surface energy of the composite particle structure can promote the formation of a smoother film layer surface of a composition of ethylene vinyl acetate and polyvinyl methyl ether, and the smoother film layer surface greatly reduces the retention time of dust and other pollutants on the surface of the film layer in most application environments, and thus dust and other pollutants cannot form aggregation in a short period of time. In most application environments, dust and other pollutants will be removed by gravity due to the smoothing effect and hydrophobic properties of the surface, thereby obtaining excellent film layer self-cleaning, waterproofing, aging resistance, corrosion resistance and other properties.
[0055] 4. A highly transparent insulating anti-corrosion heat dissipation self-cleaning film provided in the present application, the added compound functional additives can effectively assist in improving the mechanical properties of the film layer, and can effectively ensure the anti-corrosion, waterproof, salt resistance, aging resistance and other properties of the highly transparent insulating anti-corrosion heat dissipation self-cleaning film. Epoxy block polyether and polyethylene glycol methyl ether can enhance the molecular network construction assistance effect of the overall functional additives in the film material by embedding the effect of different molecular chain lengths, thereby enhancing the tightness of the internal three-dimensional network of the film layer, and molecular chains of different lengths can easily form entanglements with each other, which helps to improve the intermolecular force, thereby helping to improve the mechanical properties of the film layer, and the addition of aromatic phenol polyoxyethylene ether can effectively reduce the agglomeration of each nanoparticle added in the present application, so that the epoxy block polyether and polyethylene glycol methyl ether can be better used as dispersion carriers in the formation of the film layer, thereby enhancing the uniformity of each particle in the film layer, and can avoid the formation of large particle micropores caused by particle agglomeration, thereby affecting the connection between molecules and particles, and finally reducing the friction mechanical properties. DETAILED DESCRIPTION
[0056] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0057] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0058] Example 1
[0059] Example 1 The first aspect provides a highly transparent insulating, anti-corrosion, heat-dissipating and self-cleaning film. The raw materials, in parts by mass, are: 34.6 parts of base emulsion, 39.5 parts of nanoparticles, 15.5 parts of functional additives, 24.8 parts of diluents, 21 parts of silicone oil, 2.2 parts of leveling agents, 3.8 parts of wetting agents, and 2.5 parts of dispersants.
[0060] The basic emulsion is a composition of modified acrylic emulsion, ethylene vinyl acetate and polyvinyl methyl ether, and the mass ratio of the three is (2-5): (0.8-1.2); (0.5-1.0).
[0061] The modified acrylic emulsion is an organic siloxane modified acrylic emulsion.
[0062] The nanoparticles are modified nano-barium sulfate, nano-silicon nitride, nano-zinc oxide, nano-cerium oxide, nano-aluminum oxide and nano-zirconium oxide in a mass ratio of (2-2.5): (1.5--2): (1-1.4): (1-1.4): (1-1.4): (1-1.4);
[0063] The particle size of nano-alumina is 15-20nm, and the particle size of nano-zirconia is 15-20nm.
[0064] The preparation method of the modified nano barium sulfate comprises the following steps: adding barium sulfate into a mixed solvent: dimethylformamide and dihexylene triamine pentyl acetic acid (DTPA), dispersing into a solution, adding a modifier to modify the barium sulfate, and finally filtering, drying, sieving, and airflow classification to obtain the modified nano barium sulfate.
[0065] The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0066] The average particle size of the modified nano-barium sulfate is 20-30 nm.
[0067] The functional additive is a composition of polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether, and the mass ratio of the three is 4.3:3.2:1.4.
[0068] The weight average molecular weight of polyethylene glycol methyl ether is 400Da.
[0069] The weight average molecular weight of the epoxy block polyether is 7800Da, and the ethylene oxide block content is 70wt%.
[0070] The aromatic phenol polyoxyethylene ether is a composition of phenylethylphenol polyoxyethylene ether and trimethylstyrenephenol polyoxyethylene ether, and the mass ratio of the two is 3.6:0.8.
[0071] The HLB value of phenylethylphenol polyoxyethylene ether is 11, and the HLB value of trimethylstyrenephenol polyoxyethylene ether is 1;
[0072] The diluent is 95wt% ethanol; the leveling agent is organic silicone leveling agent BYK-306.
[0073] The wetting agent is a non-ionic wetting agent; the powder is acrylic BYK-163.
[0074] The second aspect of this embodiment provides a method for preparing a highly transparent insulating, anti-corrosion, heat-dissipating and self-cleaning film, and the specific steps include the following steps: S1: Add diluent, functional additives, silicone oil and base emulsion into a high-speed mixer, and stir at 1500rpm for 15 minutes until uniform; S2: After adding the nanoparticles, continue to maintain a speed of 1500rpm and stir for 20 minutes; S3: Finally, add leveling agent, wetting agent and dispersant at a speed of 1000rpm, stir for 9 minutes, and after completion, apply the mixture on the desired substrate surface, heat to 70°C and cure for 5.5 hours to obtain the film.
[0075] Example 2
[0076] Example 2 The first aspect provides a highly transparent insulating, anti-corrosion, heat-dissipating and self-cleaning film. The raw materials, in parts by mass, are: 30.5 parts of base emulsion, 35.6 parts of nanoparticles, 14.2 parts of functional additives, 24.8 parts of diluents, 21 parts of silicone oil, 2.2 parts of leveling agents, 3.8 parts of wetting agents, and 2.5 parts of dispersants.
[0077] The basic emulsion is a composition of modified acrylic emulsion, ethylene vinyl acetate and polyvinyl methyl ether, and the mass ratio of the three is (2-5): (0.8-1.2); (0.5-1.0).
[0078] The modified acrylic emulsion is an organic siloxane modified acrylic emulsion with a viscosity of 240 mPa·s, a solid content of 52.2 wt % at 25°C,
[0079] The nanoparticles are modified nano-barium sulfate, nano-silicon nitride, nano-zinc oxide, nano-cerium oxide, nano-aluminum oxide and nano-zirconium oxide in a mass ratio of (2-2.5): (1.5--2): (1-1.4): (1-1.4): (1-1.4): (1-1.4);
[0080] The particle size of nano-barium sulfate is 10-20nm. The particle size of nano-silicon nitride is 10-20nm.
[0081] The particle size of nano zinc oxide is 10-20nm. The particle size of nano cerium oxide is 10-20nm.
[0082] The particle size of nano-alumina is 10-20nm, and the particle size of nano-zirconia is 10-20nm.
[0083] The preparation method of the modified nano barium sulfate comprises the following steps: adding barium sulfate into a mixed solvent: dimethylformamide and dihexylene triamine pentyl acetic acid (DTPA), dispersing into a solution, adding a modifier to modify the barium sulfate, and finally filtering, drying, sieving, and airflow classification to obtain the modified nano barium sulfate.
[0084] The silane coupling agent is γ-glycidyloxypropyltrimethoxysilane.
[0085] The average particle size of the modified nano-alumina is 15-20nm.
[0086] The functional additive is a composition of polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether, and the mass ratio of the three is 4.3:3.2:1.4.
[0087] The weight average molecular weight of polyethylene glycol methyl ether is 400 Da, and the product of the corresponding molecular weight model is purchased from Haian Petrochemical Company in Jiangsu Province.
[0088] The weight average molecular weight of the epoxy block polyether is 7800 Da, the ethylene oxide block content is 70 wt %, and the epoxy block polyether is purchased from BASF with the ethylene oxide-propylene oxide block copolymer product of model L87.
[0089] The aromatic phenol polyoxyethylene ether is a composition of phenylethylphenol polyoxyethylene ether and trimethylstyrenephenol polyoxyethylene ether, and the mass ratio of the two is 3.6:0.8.
[0090] The HLB value of phenylethylphenol polyoxyethylene ether is 11, and the HLB value of trimethylstyrenephenol polyoxyethylene ether is 16.
[0091] The diluent is 95wt% ethanol; the leveling agent is organic silicone leveling agent BYK-306.
[0092] The wetting agent is a nonionic wetting agent and the dispersing agent is acrylic BYK-163.
[0093] The second aspect of this embodiment provides a method for preparing a highly transparent insulating, anti-corrosion, heat-dissipating and self-cleaning film, and the specific steps include the following steps: S1: Add diluent, functional additives, silicone oil and base emulsion into a high-speed mixer, and stir at 1500rpm for 15 minutes until uniform; S2: After adding the nanoparticles, continue to maintain a speed of 1500rpm and stir for 20 minutes; S3: Finally, add leveling agent, wetting agent and dispersant at a speed of 1000rpm, stir for 9 minutes, and after completion, apply the mixture on the desired substrate surface, heat to 70°C and cure for 5.5 hours to obtain the film.
[0094] Comparative Example 1
[0095] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being: a highly transparent insulating, anti-corrosion, heat-dissipating and self-cleaning film, wherein the raw materials are, by mass, 46.8 parts of a base emulsion, 25.8 parts of nanoparticles, 15.5 parts of a functional additive, 24.8 parts of a diluent, 21 parts of silicone oil, 2.2 parts of a leveling agent, 3.8 parts of a wetting agent and 2.5 parts of a dispersant.
[0096] Comparative Example 2
[0097] The specific implementation method of this comparative example is basically the same as that of Example 1, with the only difference being: a highly transparent insulating, anti-corrosion, heat-dissipating and self-cleaning film, wherein the raw materials, in parts by mass, are: 40.6 parts of base emulsion, 39.5 parts of nanoparticles, 5.6 parts of functional additives, 24.8 parts of diluent, 21 parts of silicone oil, 2.2 parts of leveling agent, 3.8 parts of wetting agent and 2.5 parts of dispersant.
[0098] Comparative Example 3
[0099] The specific implementation of this comparative example is basically the same as that of Example 1, except that the mass ratio of the modified acrylic emulsion and is 4:0.6.
[0100] Comparative Example 4
[0101] The specific implementation of this comparative example is basically the same as that of Example 1, except that the mass ratio of modified nano-barium sulfate, nano-aluminum oxide and nano-zirconium oxide is 0.5:2.5:2.2.
[0102] Comparative Example 5
[0103] The specific implementation of this comparative example is basically the same as that of Example 1, except that the functional additive is a composition of polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether, and the mass ratio of the three is 8:2:0.3.
[0104] Performance Evaluation
[0105] 1. Mechanical properties: Samples with a thickness of 0.2 mm, a length of 2 cm, and a width of 1 cm were taken from the highly transparent insulating, anti-corrosion, heat-dissipating, and self-cleaning films prepared in the embodiments and comparative examples, and tensile strength and elongation at break were tested using a universal tensile machine. The test values were taken as the average of 10 tests and recorded in Table 1.
[0106] 2. Self-cleaning performance: Samples with a thickness of 0.2 mm, a length of 2 cm, and a width of 1 cm were taken from the self-cleaning films prepared in the embodiments and comparative examples, and placed in an outdoor environment for 6 months in a fixed test group. The average environmental range was 26.8-28.2°C, and the average relative humidity range was 66.4-70.1%. After 6 months, the samples were taken back and naturally rinsed with clean water. The surface of the self-cleaning film sample was randomly cut to detect the percentage of dirt occupying the area. The test value was the average value of 10 tests and recorded in Table 1.
[0107] 3. Waterproof performance: For the self-cleaning membranes prepared in the embodiments and comparative examples, samples with a thickness of 0.2 mm, a length of 2 cm, and a width of 1 cm were taken, and the water contact angle on the membrane surface was tested by the sessile drop method. The test water droplet was 2.5 μL, and the test time was 15 s. The test value was the average of 10 tests and recorded in Table 1.
[0108] 4. Aging resistance: For the self-cleaning films prepared in the embodiments and comparative examples, samples with a thickness of 0.2 mm, a length of 2 cm, and a width of 1 cm were taken and placed in a constant temperature and humidity chamber at 68±3°C and a relative humidity of 75±2%. They were stored for 3 months and taken out after 3 months. The tensile strength of the film layer was tested before and after 3 months (tested by the performance test 1 method), and the retention rate of tensile strength was calculated. Retention rate % = (tensile strength of the film layer after 3 months / tensile strength of the film layer before 3 months) × 100%. The test values were taken as the average value of 10 tests and recorded in Table 1.
[0109] 5. Corrosion resistance: Samples with a thickness of 0.2 mm, a length of 2 cm, and a width of 1 cm were taken from the self-cleaning films prepared in the embodiments and comparative examples, and a salt spray corrosion resistance test was performed with 5 wt % NaCl. The samples were immersed in 5 wt % NaCl for 800 h. After the test, the samples were taken out to observe whether there were obvious film damage, tearing, corrosion oxidation, and curling. The tensile strength retention rate was tested again using the scheme in performance test 4. If there were no obvious above-mentioned phenomena and the tensile strength retention rate was ≥85%, it was considered qualified, otherwise it was considered unqualified. The qualified rate results of 50 samples in each group were recorded in Table 1.
[0110] Table 1 Performance test results
[0111]
[0112]
[0113] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 and 2 of the present application have obvious advantages over comparative examples 1 to 5 in terms of mechanical properties, self-cleaning properties, waterproof properties, salt resistance, aging resistance, corrosion resistance and other properties. This is mainly because the functional additives, composite nanoparticles and other matching technical solutions specified in the present application work together, while comparative examples 1 to 5 do not adopt the technical solutions specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests, which further proves the necessity of the technical solutions specified in the present application for the technical effects of the present application and solving technical problems.
Claims
1. A highly transparent insulating, anti-corrosion, heat-dissipating and self-cleaning coating film, characterized in that: The raw materials are as follows: 20-40 parts of base emulsion, 30-60 parts of nanoparticles, 10-20 parts of functional additives, 20-30 parts of diluents, 2-5 parts of silicone oils, 1-3 parts of leveling agents, 2-5 parts of wetting agents, and 1-3 parts of dispersants, in parts by mass. The base emulsion is a composition of modified acrylic emulsion, ethylene vinyl acetate and polyvinyl methyl ether; the mass ratio of the modified acrylic emulsion, ethylene vinyl acetate and polyvinyl methyl ether is (2-5): (0.8-1.2); (0.5-1.0) The modified acrylic emulsion is an organosiloxane-modified acrylic emulsion; The nanoparticles are a composition of modified nano barium sulfate, nano silicon nitride, nano zinc oxide, nano cerium oxide, nano aluminum oxide and nano zirconium oxide; The mass ratio of the modified nano-barium sulfate, nano-silicon nitride, nano-zinc oxide, nano-cerium oxide, nano-aluminum oxide and nano-zirconium oxide is (2-2.5): (1.5--2): (1-1.4): (1-1.4): (1-1.4): (1-1.4); The preparation method of the modified nano barium sulfate comprises the following steps: adding nano barium sulfate to a mixed solvent: dimethylformamide and dihexylene triamine pentane acetic acid (DTPA), dispersing into a solution, adding a modifier to modify the barium sulfate, and finally filtering, drying, sieving, and airflow classification to obtain the modified nano barium sulfate. The mass ratio of the modified nano-barium sulfate, nano-silicon nitride, nano-zinc oxide, nano-cerium oxide, nano-aluminum oxide and nano-zirconium oxide is (2-2.5): (1.5--2): (1-1.4): (1-1.4): (1-1.4): (1-1.4); The average particle size of the modified nano-barium sulfate is 20-30 nm; The average particle size of the nano silicon nitride is 10-20 nm; The average particle size of the nano zinc oxide is 10-20 nm; The average particle size of the nano cerium oxide is 10-20 nm; The average particle size of the nano-alumina is 10-20 nm; The average particle size of the nano zirconium oxide is 10-200 nm; The functional additive is a composition of polyethylene glycol methyl ether, epoxy block polyether and arylphenol polyoxyethylene ether; The mass ratio of the polyethylene glycol methyl ether, epoxy block polyether and aromatic phenol polyoxyethylene ether is (4-5): (3-3.5): (1-2).
2. According to claim 1, it is characterized in that: The mass ratio of the basic emulsion, the nanoparticles and the functional additive is (30-38): (35-45): (12-18).
3. The highly transparent insulating anti-corrosion heat dissipation self-cleaning film according to claim 2 is characterized by: The mass ratio of the base emulsion, the diluent and the silicone oil is (30-38): (22-26): (18-24).
4. The highly transparent insulating anti-corrosion heat dissipation self-cleaning film according to claim 3 is characterized by: The average particle size of the nano-alumina is 10-20 nm.
5. The highly transparent insulating anti-corrosion heat dissipation self-cleaning film according to claim 4, characterized in that: The average particle size of the nano zirconium oxide is 10-20 nm.
6. The highly transparent insulating anti-corrosion heat dissipation self-cleaning film according to claim 6, characterized in that: The weight average molecular weight of the polyethylene glycol methyl ether is 400-800 Da.
7. The highly transparent insulating anti-corrosion heat dissipation self-cleaning film according to claim 7, characterized in that: The weight average molecular weight of the epoxy block polyether is 6000-8000 Da.
8. A method for preparing a highly transparent insulating, anti-corrosion, heat-dissipating and self-cleaning film according to any one of claims 1 to 8, characterized in that: The specific steps include the following steps: S1: Add diluent, functional additive, silicone oil and base emulsion into a high-speed mixer, and stir at 1200-1800 rpm for 10-20 minutes until uniform; S2: After adding the nanoparticles, continue to maintain a speed of 1200-1800 rpm and stir for 15-25 minutes; S3: Finally, add leveling agent, wetting agent and dispersant at a speed of 800-1000 rpm, stir for 8-10 minutes, and after completion, apply the mixture on the desired substrate surface, heat to 60-80°C and cure for 4-6 hours; or dry and cure for 24 hours; the result is obtained.
9. A highly transparent insulating, anti-corrosion, heat-dissipating and self-cleaning film according to any one of claims 1 to 8 meets the diverse performance requirements for insulation, anti-corrosion, heat-dissipating and self-cleaning in the fields of electronic components, electronic products, engines, motors, cabinets, wires and cables, boilers, high-temperature pipelines, etc., achieves good comprehensive performance and long service life, has good energy-saving effects, reduces the cost of use, and has very excellent application prospects.
10. Where the patented invention is an innovative application of the best performance of various materials, products with similar performance can be produced by recombining the materials with the patented invention formula, without reducing the variety of materials or the content of materials, and are also protected by the patented invention and cannot be imitated.